Real-time gastrointestinal infection surveillance through a cloud-based network of clinical laboratories - Ruzante, Juliana M.; Olin, Katherine; Munoz, Breda; Nawrocki, Jeff; Selvarangan, Rangaraj; Meyers, Lindsay (PloS one, 2021)
Acute gastrointestinal infection (AGI) represents a significant public health concern. To control and treat AGI, it is critical to quickly and accurately identify its causes. The use of novel multiplex molecular assays for pathogen detection and identification provides a unique opportunity to improve pathogen detection, and better understand risk factors and burden associated with AGI in the community. In this study, de-identified results from BioFire ® FilmArray ® Gastrointestinal (GI) Panel were obtained from January 01, 2016 to October 31, 2018 through BioFire ® Syndromic Trends (Trend), a cloud database. Data was analyzed to describe the occurrence of pathogens causing AGI across United States sites and the relative rankings of pathogens monitored by FoodNet, a CDC surveillance system were compared. During the period of the study, the number of tests performed increased 10-fold and overall, 42.6% were positive for one or more pathogens. Seventy percent of the detections were bacteria, 25% viruses, and 4% parasites. Clostridium difficile , enteropathogenic Escherichia coli (EPEC) and norovirus were the most frequently detected pathogens. Seasonality was observed for several pathogens including astrovirus, rotavirus, and norovirus, EPEC, and Campylobacter . The co-detection rate was 10.2%. Enterotoxigenic E . coli (ETEC), Plesiomonas shigelloides , enteroaggregative E . coli (EAEC), and Entamoeba histolytica were detected with another pathogen over 60% of the time, while less than 30% of C . difficile and Cyclospora cayetanensis were detected with another pathogen. Positive correlations among co-detections were found between Shigella /Enteroinvasive E . coli with E . histolytica , and ETEC with EAEC. Overall, the relative ranking of detections for the eight GI pathogens monitored by FoodNet and BioFire Trend were similar for five of them. AGI data from BioFire Trend is available in near real-time and represents a rich data source for the study of disease burden and GI pathogen circulation in the community, especially for those pathogens not often targeted by surveillance.